Boron nitride nanotubes as vehicles for intracellular delivery of fluorescent drugs and probes. (March 2016) - Niskanen, Jukka; Zhang, Issan; Xue, Yanming; Golberg, Dmitri; Maysinger, Dusica; Winnik, Françoise M
Aim: To evaluate the response of cells to boron nitride nanotubes (BNNTs) carrying fluorescent probes or drugs in their inner channel by assessment of the cellular localization of the fluorescent cargo, evaluation of the in vitro release and biological activity of a drug (curcumin) loaded in BNNTs.Methods: Cells treated with curcumin-loaded BNNTs and stimulated with lipopolysaccharide were assessed for nitric oxide release and stimulation of IL-6 and TNF-α. The cellular trafficking of two cell-permeant dyes and a non-cell-permeant dye loaded within BNNTs was imaged.Results: BNNTs loaded with up to 13 wt% fluorophores were internalized by cells and controlled release of curcumin triggered cellular pathways associated with the known anti-inflammatory effects of the drug.Conclusion: The overall findings indicate that BNNTs can function as nanocarriers of biologically relevant probes/drugs allowing one to examine/control their local intracellular localization and biochemical effects, leading the way to applications as intracellular nanosensors.